Perception and practices of farmers on the utilization of sweetpotato, and other root tubers, and banana for pig feeding in smallholder crop-livestock systems in Uganda - Dione, Michel M.; Pezo, P.; Kyalo, Gerald; Mayega, L.; Nadiope, G.; Lukuyu, Ben A. (2015)
Limited access to quality feeds and reliable feed supply are amongst the priority constraints of smallholder pig production in Uganda. Among the feeds given to pigs, sweetpotato (SP), banana and other root tubers residues are common. However, information on farmers’ perceptions and practices on the proper use of these residues for pig feeding is limited. Therefore, this study aimed at assessing those aspects, as well as to identify opportunities for better use of these residues in the pig-SP systems. A qualitative survey was undertaken in Masaka and Kamuli, two districts of Uganda with high pig population and SP production. Focus Group Discussions (FGD) and Key Informant Interviews (KII) were undertaken with 80 small scale pig and SP producers and 24 key informants. Results from this study revealed that the majority of pig farmers in those districts use SP and other RTB crop residues as animal feed. During the rainy season, farmers scored high the utilization of SP crop residues, with the latter being the leading contributor to the pig diet especially in the rural area. SP crop residues are usually fed to pigs fresh without processing. Among the residues, fresh raw vines represent the largest part fed to pig (70%), as compared to roots and peels. The way these residues are offered vary, for example in peri-urban areas with easier access to commercial feeds, farmers feed the crop residues mixed with concentrates; whereas in rural areas with limited access to commercial feeds, crop residues tend to be given without supplementation. However, the full potential of SP and other RTB crop residues for pig feeding is not yet fully exploited as farmers accept that a large amount is wasted (37% in Masaka and 40% in Kamuli). In Masaka, the proportion of SP crop residues utilized at household level mostly for pig feeding was 40%, while in Kamuli was 52%. This study demonstrated that there is potential for better use of SP and other RTB crop residues as pig feed in the smallholder pig farming systems in Uganda, but the major constraint as pointed out by farmers is the poor access to technologies for preserving these resources. Therefore, there is a need for further exploration of strategies for conserving SP and other RTB crop residues during the harvesting period for use in pig feeding during times of feed scarcity.